O regime constitucional da contribuição de intervenção do domínio econômico aplicável ao setor de combustíveis - Marinho, Karoline Lins Camara (2008)
The performance of the State in the economic area is only legitimized when to be given in virtue of the protection of the principles established constitutionally. Thus, the economic intervention of the State prioritizes the formation of a joust economic order and in this context, it fulfills to us to define, to the long one of this work, the contours of the intervention of the State in the economic domain in the presence of the Federal Constitution of the Republic of 05 of October of 1988, and, more specifically, in the petroliferous economic sector by means of the interventive contribution instituted after the Constitutional amendment 33/2001, with Law 10.336/2001. With the creation of this institute, in Brazil, emerged innumerable quarrels concerning its constitutional legitimacy, directing uncurling of the research to the study of the state intervention through this contribution and its constitutional limits, in the purpose to demonstrate the parameters for its institution and application. In this way, the interventive contribution in the fuel sector (CIDE-Combustíveis) shows itself as an intervention instrument on the economic domain, acting in way to finance the indirect performance of the State, specially in what concerns to the promotion of the principle of sustainable development principle. Therefore, CIDE-Combustíveis is an able instrument to concretizes the mentioned constitutional principle. Thus, the division of its incomes promotes the consolidation of the principle of the cooperative federalism. In this direction, from premises of the environmental tax law, this intends to demonstrate the utility and constitutionality of this exaction tax, primordially with regard to the realization of the basic right to the balanced environment